Library Document and Resource Centers as Important Information Institutions in the Conditions of International Military Confrontation in Ukraine - Horovyi Valery (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
Characteristic feature of modern interstate international confrontations, especially at the military level, is the growing mutual opposition not only of military formations, special information organizations and employees of defense enterprises, but also of the entire mass of the civilian population. With the development of electronic information technologies, the activation of globalization processes, new operational information becomes the acquisition of all categories of population’ consciousness. With its help, public opinion is consciously formed today, which becomes an intellectual weapon of the opposing parties. Libraries, accumulating socially significant electronic information resources, structuring them and preparing them for effective use, become important tools of quality information use. The proposed article summarizes the main trends in the development of qualitatively new technologies related to the formation of an electronic information resource and its effective use.